Medical Quality Management Theory and Practice - Giardino, Angelo P.; Riesenberg, Lee Ann.; Varkey, Prathibha; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This comprehensive medical textbook is a compendium of the latest information on healthcare quality. The text provides knowledge about the theory and practical applications for each of the core areas that comprise the field of medical quality management as well as insight and essential briefings on the impact of new healthcare technologies and innovations on medical quality and improvement. The third edition provides significant new content related to medical quality management and quality improvement, a user-friendly format, case studies, and updated learning objectives. This textbook also serves as source material for the American Board of Medical Quality in the development of its core curriculum and certification examinations. Each chapter is designed for a review of the essential background, precepts, and exemplary practices within the topical area: Basics of Quality Improvement Data Analytics for the Improvement of Healthcare Quality Utilization Management, Case Management, and Care Coordination Economics and Finance in Medical Quality Management External Quality Improvement $1 (BAccreditation, Certification, and Education The Interface Between Quality Improvement and Law Ethics and Quality Improvement With the new edition of Medical Quality Management: Theory and Practice, the American College of Medical Quality presents the experience and expertise of its contributors to provide the background necessary for healthcare professionals to assume the responsibilities of medical quality management in healthcare institutions, provide physicians in all medical specialties with a core body of knowledge related to medical quality management, and serve as a necessary guide for healthcare administrators and executives, academics, directors, medical and nursing students and residents, and physicians and other health practitioners.s
Chapter 1. Introduction -- Chapter 2. Basics of Quality Improvement -- Chapter 3. Quality Measurement -- Chapter 4. Patient Safety -- Chapter 5. Health Informatics -- Chapter 6. Data Analytics for the Improvement of Health Care Quality -- Chapter 7. Utilization Management, Case Management, and Care Coordination -- Chapter 8. Organization Design and Management -- Chapter 9. Economics and Finance in Medical Quality Management -- Chapter 10. External Quality Improvement$1 (BAccreditation, Certification, and Education -- Chapter 11. The Interface Between Quality Improvement and Law -- Chapter 12. Ethics and Quality Improvement. .s
Keywords: Health administration; Health care management; Health services administration; Practice of medicine; Medical care; Public health; Health Administration; Health Care Management; Practice and Hospital Management; Health Services Research